The Role of Liquid Biopsy for Detecting Epidermal Growth Factor Receptor (EGFR) Mutations in Patients with Advanced Non-Small Cell Lung Cancer (NSCLC) – A Preliminary Study in Indonesian Population - Agus Susanto Kosasih; Arif Riswahyudi Hanafi; Ninik Sukartini; Mariska Pangaribuan; Muhammad Alfin Hanif; Willy Pandu Ariawan; Sri Agustini Kurniawati; Dian Cahyanti; Kartika Anastasia Kosasih; Alyssa Diandra; Markus Yovian; Lyana Setiawan (http://dharmais.co.id/, 2023)
Background: The development of new biomarker-targeted therapies is associated with the improvements in overall survival of advanced non-small cell lung cancer (NSCLC) sufferers. However, tissue biopsy as the gold standard to determine tumor molecular status is not always feasible in advanced diseases. Liquid biopsy, a minimally invasive technique to obtain cytological and molecular assessment from patients allows real-time monitoring of tumors and identification of resistant mechanisms. Therefore, this preliminary study aimed to compare the molecular profile of advanced NSCLC from liquid and tissue biopsy.Methods: This cross-sectional study was conducted on patients with NSCLC undergoing diagnostic procedures at Dharmais National Cancer Center Hospital from January 2018 to December 2021. Tissue biopsy to check epidermal growth factor receptor (EGFR) mutations was performed on formalin-fixed paraffin-embedded (FFPE) tissue blocks. Analysis of mutations involved using a home-brew polymerase chain reaction (PCR) based on a high-resolution melting technique. Meanwhile, the liquid biopsy was performed using blood samples, and sequencing for circulating tumor DNA (ctDNA) was carried out with NGS.Results: : The results showed that among the 22 subjects enrolled in the study, tissue biopsy identified wild-type EGFR in 18 (81.8%), exon 19 mutations in 3, and exon 21 mutations (L861Q and L858R) in 3. Liquid biopsy found EGFR exon 19 deletions in 11 samples (50%), exon 21 mutations (L861Q and L858R) in 10, L861Q in 7, L8585 in 6, and wild type in 1 sample. Additionally, acquired EGFR mutations in exon 20 T790M were found in 5 samples.Conclusions: Liquid biopsy may be beneficial in patients for whom tissue biopsy cannot be performed or where tissue for molecular profiling is inadequate. This modality can also be used to detect molecular resistance in patients with advanced NSCLC.